Living with Climate Change: Assessment of the Adaptive Capacities of Smallholders in Central Rift Valley, Ethiopia - Mekonnen, Z.; Kassa, H. (Scientific Research Publishing, Inc., 2019)
Farms less than 2 hectares have constituted almost 90% of the total number of farms in Ethiopia. These small farms are rain fed and are vulnerable to climate change and variability extremes such as droughts. This in turn undermined the ability of smallholders’ farmers to feed themselves and the growing population. A questionnaire survey was conducted with a random sample of 355 smallholder farmers distributed in three agro-ecologies, namely, lowland, midland, and highland in central rift valley of Ethiopia (Arsi Negele district). This was supplemented with 18 focus group discussions and 30 key informant interviews. How do smallholder farmers live with climate change and variability challenges? On the basis of this question, this study has assessed the factors that determine the adaptive capacities, strategies and livelihoods of smallholders to climate change and variability; and the role of climate capacities and landscape functions for sustainable adaptation in response to climate change and variability. The results showed that even if most respondents (>95%) have the perception and intention of climate change; it was nearly 3% of them have higher adaptive capacity to adapt to climate change impacts. Adaptive capacity of smallholders and the potential impact exerted by climate change risks were negatively correlated (r = −0.134 and p < 0.02). The results showed that farmers have made some evolution in their livelihoods as an adaptation strategy. Adaptation strategies explicitly depend on adaptive capacity-human, natural, financial, social and physical resources. Indeed, the results indicated limited climate-specific and climate-relevant capacities at the local level which suggests a need to strengthen climate capacities. Moreover, it has been implicated that maintaining the landscapes, which provide landscape production functions that build the well-being and adaptive capacity of farmers, could help to sustain farmers’ livelihood and build their adaptive capacity to withstand the challenges of climate change.